Physico-Mechanical and Tableting Properties of Metronidazole Obtained by Crystallo Co-Agglomeration Technique (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Due to its simplicity and cost-effectiveness, direct compression has become the approach most frequently used to create tablet. Nonetheless, the active pharmaceutical ingredient should have acceptable flow and good compaction qualities in order to use direct compression in tablet manufacture. Crystallo co-agglomeration (CCA) technique has shown to be efficient in improving the earliest stages of tablet manufacture. By combining crystallization (primary particles design) and agglomeration (secondary particles design), it increases the product’s added value.Objectives: This study exploits the CCA approach to boost the physico-mechanical and tableting properties of metronidazole tablet.Methods: Metronidazole co-agglomerates was formulated with hydrophilic polymers using CCA technique. The dilution potential of the produced agglomerates was assessed to obtain suitable concentration that was used to prepare metronidazole tablet by direct compression method after which the tablet properties were evaluated.Results: Metronidazole agglomerate powder had a very good flow rate and angle of repose, low bulk and tapped densities as well as improved Carr’s compressibility index, 15.00±0.14% and Hausner’s ratio 1.18±0.03 compared to pure metronidazole (27.54±0.14% and 1.38±0.04 respectively). The CSFR/Dt ratio for batches F3 and F4 showed higher compactability and functionality.  The dissolution profiles of batches F3 and F4 of metronidazole exhibited improved dissolution behaviour than pure drug containing batches (batches F1 and F2).Conclusion: The CCA technique yielded metronidazole with increased particle size and compactability resulting in excellent flowability and packability due to reduced inter-particulate friction, which exhibited improved compressibility, dilution potential, disintegration and dissolution rate.